Elevada proporción de Staphylococcus aureus meticilino resistentes aislados en pacientes atendidos en un servicio ambulatorio dermatológico de referencia nacional: cohorte 2010 a 2019 - Elkin Javier Casadiego Rincón (Asociación Colombiana de Infectología, 2020)
Objective: To estimate the resistance trend of Staphylococcus aureus (S. aureus) against different antibiotics in a reference dermatology outpatient center in Colombia. Methods: Descriptive and trend analyzes were performed using segmented regression models for the period 2010 to 2019.Results: The greatest resistance was presented to oxacillin, with a median of 54.3% (RIQ: 43 - 58.8), followed by erythromycin with 20%, (RIQ: 15.4 - 26.5), then clindamycin with 14% (RIQ: 7.9 - 20), gentamicin with 7.5% (RIQ: 0 -10), trimethoprim / sulfamethoxazole (SXT) with 5.5% (RIQ: 4 - 11), and ciprofloxacin with 2.1% (RIQ: 2 - 8.4). The trend of S. aureus resistance to oxacillin from 2010 to 2019 was increasing with a non-significant Annual Percent Change (APC) of (0.07) (95% CI -3.7, 3.9). APC for erythromycin (-1.2) (95% CI: -11.3; 10), clindamycin (-1.7) (95% CI: 11; -12.9), ciprofloxacin (-25.4) (95% CI: -44.6; 0.5) and trimethoprim / sul-famethoxazole (-20.7) (95% CI: -43.5; 11.2), were decreasing not significant. For gentamicin the trend was decreasing and significant (-44.2) (95% CI: -19.9; -61.1).Conclusions: The resistance of S. aureus to oxacillin exhibited a slightly increasing trend for the period 2010 to 2019 and increasing in the last 3 years, exceeding on average that reported at the country level and the world average. Antibiotics for outpatient management of skin and soft tissue pyoderma with less resistance were ciprofloxacin, SXT, clindamycin for systemic use, and fusidic acid, mupirocin for topical management and decolonization. It is important to articulate surveillance of S. aureus in outpatient care to the national surveillance network.